Neurocardiology: Major mechanisms and effects - Swenne, Cees A.; Shusterman, Vladimir (Journal of electrocardiology, 2025)
Neurocardiology is a broad interdisciplinary specialty investigating how the cardiovascular and nervous systems interact. In this brief introductory review, we describe several key aspects of this interaction with specific attention to cardiovascular effects. The review introduces basic anatomy and discusses physiological mechanisms and effects that play crucial roles in the interaction of the cardiovascular and nervous systems, namely: the cardiac neuraxis, the taxonomy of the nervous system, integration of sensory input in the brainstem, influences of the autonomic nervous system (ANS) on heart and vasculature, the neural pathways and functioning of the arterial baroreflex, receptors and ANS effects in the walls of blood vessels, receptors and ANS effects in excitable cells in the heart, ANS effects on heart rate and sympathovagal balance, endo-epicardial inhomogeneity, ANS effects with a balanced vagal and sympathetic stimulation, sympathovagal interaction, arterial baroreflex, baroreflex sensitivity and heart rate variability, arrhythmias and the arterial baroreflex, the cardiopulmonary baroreflex, the exercise pressor reflex, exercise-recovery hysteresis, mental stress, cardiac-cardiac reflexes, the cardiac sympathetic afferent reflex (CSAR), and neuromodulation. Also, the potential role of the discussed mechanisms in cardiovascular disorders will be touched upon.